Mewujudkan Desa Mandiri Melalui Pelestarian Lingkungan dan Digitalisasi di Desa Deah Glumpang Kota Banda Aceh - Yana, Saifuddin; Susanti; Nelly; Syamsuddin, Nurfiani; Hanum, Filia; Juwita (PASAI : Jurnal Pengabdian kepada Masyarakat, 2022)
Digital transformation which has become a new platform in almost all aspects of human life today has caused rapid changes throughout the world. Higher education institutions that focus on scientific research and development, become important agents for society to transform this technology to improve people's lives. The role of Higher Education in transferring this technological knowledge to society is one of the KPIs (Main Performance Indicators) stipulated through Kepmendikbud No 03/M/2021. the results of the lecturer's work are used by the community or get recognition through collaborative study programs, in this case with partners, namely Deah Glumpang Village, Meuraxa Banda Aceh sub-district, the dedication resulted in a cooperation agreement between the Faculty of Economics, Serambi Mekkah University and Deah Glumpang village, the Community, especially Small and Medium Enterprises assisted in making NIB (Business Identification Number), basic food assistance for participating communities and assisting villages in preserving the environment through planting mangrove trees to avoid abrasion and flooding in villages where most of the area is coastal.